Decorin Suppresses Invasion and EMT Phenotype of Glioma by Inducing Autophagy via c-Met/Akt/mTOR Axis - Jia, Yanfei; Feng, Qian; Tang, Bo; Luo, Xiaodong; Yang, Qiang; Yang, Hu; Li, Qiang (Frontiers in Oncology, 2021)
Decorin exhibits inhibitory effects in tumorigenesis in various types of cancers. The clinical characteristics of 42 patients with GBM were reviewed and analyzed. Lentiviral constructs for decorin overexpression and shRNA-mediated silencing were established for U87MG cells and T98G cells, respectively. The expressions of EMT- and autophagy-associated markers were detected in GBM cell lines. The migration and invasion of the glioma cells were assayed to reflect the malignant behavior of GBM. A mouse xenograft model was used to verify the effect of decorin on autophagy in vivo. Reduced expression of decorin in glioma tissues was associated with a poor survival of the patients. Decorin overexpression suppressed cell migration, invasion and attenuated EMT phenotype in glioma cell lines. Further study indicated that decorin inhibited EMT phenotype through the induction of autophagy. The mechanisms include inhibiting the activation of c-Met/Akt/mTOR signaling and regulating the expressions of mesenchymal markers including Slug, vimentin and Twist, and epithelial marker E-cadherin. In addition, decorin overexpression in a mice model can also suppress the GBM invasion and EMT phenotype. In conclusion, decorin suppresses invasion and EMT phenotype of glioma by inducing autophagy via c-Met/Akt/mTOR axis.